Decontamination and Management of Contaminated Hair following a CBRN or HazMat Incident. (26th June 2019) - Matar, Hazem; Pinhal, Andreia; Amer, Nevine; Barrett, Mark; Thomas, Elliot; Hughes, Philip; Larner, Joanne; Chilcott, Robert P
Abstract: This in vitro study evaluated the "triple protocol" of dry decontamination, the ladder pipe system (a method for gross decontamination), and technical decontamination for the decontamination of hair following chemical contamination. First, we assessed the efficacy of the 3 protocols, alone or in combination, on excised porcine skin and human hair contaminated with either methyl salicylate (MS), phorate (PHR), sodium fluoroacetate (SFA), or potassium cyanide (KCN). A second experiment investigated the residual hair contamination following decontamination with the triple protocol at different intervals postexposure. In a third experiment, hair decontaminated after exposure to MS or PHR was evaluated for off-gassing. Though skin decontamination was highly effective, a substantial proportion (20%–40%) of the lipophilic compounds (MS and PHR) remained within the hair. The more water-soluble contaminants (SFA and KCN) tended to form much smaller reservoirs within the hair. Interestingly, substantial off-gassing of MS, a medium volatility chemical, was detectable from triple-decontaminated hair up to 5 days postexposure. Overall, the decontamination strategies investigated were effective for the decontamination of skin, but less so for hair. These findings highlight the importance of contaminated hair serving as a source of potential secondary contamination by contact or inhalation. Therefore, consideration should be given to the removal of contaminated hair following exposure to toxic chemicals.